PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA ACCOUNT REPRESENTATIVE KPP PRATAMA MAGELANG - Sri Susilowati (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
This study aimed to examine the effect of transformational leadership style, organizational commitment, and job satisfaction on Account Representative performance of KPP Pratama Magelang. This study was quantitative research using primary and secondary data sources. The data collection method used an online questionnaire in the form of a statement with a Likert scale and sampling used purposive sampling technique. Processing of data analysis techniques used IBM SPSS Statistics 26 and data analysis methods used multiple linear regression. The results showed that the transformational leadership style did not be proven to have an effect on the Account Representative performance of KPP Pratama Magelang. Organizational commitment had a significant positive effect on the Account Representative’s performance and job satisfaction also had a significant positive effect on the Account Representative’s performance. The last, transformational leadership style, organizational commitment, and job satisfaction simultaneously had a significant positive effect on Account Representative performance of KPP Pratama Magelang.